Effects of chia (Salvia hispanica. L) on anthropometric measures and other cardiometabolic risk factors: A systematic review and dose-response meta-analysis - Sevil Kiani; Sina Naghshi; Maryam Saghafi-Asl (Elsevier, 2024)
Background: Findings of available randomized controlled trials (RCTs) on the effects of chia are inconsistent. Although previous meta-analyses summarized available findings in this regard, some limitations may distort their findings. Moreover, none of these meta-analyses examined the dose-response association of chia on cardiometabolic risk factors (CMRFs). Therefore, the present study aimed to evaluate the effect of chia consumption on CMRFs. Methods: Relevant RCTs were included by searching the ISI Web of Science, PubMed, and Scopus databases up to June 2, 2023. Mean differences (MD) and 95 % confidence intervals (CI) were pooled using random-effects model. Results: Ten publications were included in this systematic review and the meta-analysis. The results showed a significant reduction in systolic blood pressure (SBP) (MD = -7.87 mmHg; 95 % CI: − 12.92 to − 2.82; I2 = 71.3 %, P heterogeneity = 0.004), diastolic blood pressure (MD = -6.33 mmHg; 95 %CI: − 7.33 to − 5.34, I2 = 0 %, P heterogeneity = 0.42) and high-density lipoprotein cholesterol (HDL-c) (MD = -4.09 mg/dl; 95 %CI: − 6.76 to − 1.43, I2 = 12.4 %, P heterogeneity = 0.33). However, the effects of chia on the other risk factors were not significant. Based on the dose-response analysis, a 10-g/d increase in chia consumption significantly reduced SBP (MD = -2.20 mmHg; 95 %CI: − 3.75 to − 0.66, I2 = 78.9 %, P heterogeneity < 0.001) and HDL-c (MD = -1.10 mg/dl; 95 %CI: − 1.72 to − 0.49, I2 = 0 %, P heterogeneity = 0.52). Conclusion: Chia consumption might have a beneficial effect on lowering blood pressure. Chia consumption can also lead to a slight reduction in HDL-c levels. As the quality of the included studies was mostly low, the findings should be interpreted with caution. Well-designed trials with larger sample sizes and longer duration of follow-up are needed to provide additional insight into the dose-dependent effects of chia consumption.